Marketing relacji jako orientacja zwiększająca szansę powodzenia procesów restrukturyzacji i prywatyzacji placówek służby zdrowia w Polsce - Wachowicz, Renata (Relation Marketing as the Factor Increasing the Chances of Success in Restructuring and Privatization Processes of Health Centres in Poland, 2006)
The on-going reform process in health care in Poland, restructuring of health centres and consequences of joining the European Union changed radically the operating conditions in health centres. As a consequence of the irreversible restructuring process of medical services as well as the emergence of competitive private centres, the success can be achieved only by the centres which will be able to establish long-term, profitable ties with the patients and other actors in the market. Relation marketing seems to be the best solution to the problem of helath providers undergoing restructuring.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 121-134